Medical Education's Wicked Problem: Achieving Equity in Assessment for Medical Learners - Lucey, Catherine R; Hauer, Karen E; Boatright, Dowin; Fernandez, Alicia (Academic medicine, 2020)
Despite a lack of intent to discriminate, physicians educated in U.S. medical schools and residency programs often take actions that systematically disadvantage minority patients. The approach to assessment of learner performance in medical education can similarly disadvantage minority learners. The adoption of holistic admissions strategies to increase the diversity of medical training programs has not been accompanied by increases in diversity in honor societies, selective residency programs, medical specialties, and medical school faculty. These observations prompt justified concerns about structural and interpersonal bias in assessment. This manuscript characterizes equity in assessment as a "wicked problem" with inherent conflicts, uncertainty, dynamic tensions, and susceptibility to contextual influences. The authors review the underlying individual and structural causes of inequity in assessment. Using an organizational model, they propose strategies to achieve equity in assessment and drive institutional and systemic improvement based on clearly articulated principles. This model addresses the culture, systems, and assessment tools necessary to achieve equitable results that reflect stated principles. Three components of equity in assessment that can be measured and evaluated to confirm success include intrinsic equity (selection and design of assessment tools), contextual equity (the learning environment in which assessment occurs), and instrumental equity (uses of assessment data for learner advancement and selection and program evaluation). A research agenda to address these challenges and controversies and demonstrate reduction in bias and discrimination in medical education is presented.